Strengthening Diabetes Self-Management Skills in People With Diabetes Mellitus in Kapasa Raya Village - Sulfikar, Andi; Rajab, Alfian; Thalib, Abdul; Musyawir, ahmad (CV. Paperhome Indonesia, 2024)
Diabetes Militus (DM) or known as diabetes, is currently a disease that is commonly found This study highlights. The effectiveness of the counseling intervention